Fixed point theory and applications. - Cho, Yeol Je; Kim, Jong Kyu; Kang, Sin-min, 1954-; International Conference on Nonlinear Functional Analysis and Applications (8th : 2004 : Gyeongsang National University and Kyungnam University) (Hauppauge, NY : Nova Science Publishers, 2007)
Includes bibliographical references and index